Navigating the Triad of Trauma: A Case Report on Managing Concurrent Pulmonary Contusion, Traumatic Brain Injury, and Cervical Fracture in a Geriatric Patient - Yasyfie Asykari; Septian Adi Permana; Eko Setijanto (Open Access Indonesian Journal of Medical Reviews, 2025)
The management of geriatric patients with multiple severe injuries presents a formidable clinical challenge due to reduced physiological reserve and the complex interplay of competing therapeutic goals. This report details the case of a geriatric patient suffering from the triad of pulmonary contusion (PC), moderate traumatic brain injury (TBI), and an unstable cervical spine fracture, highlighting the intricate balance required in neuroprotective and lung-protective ventilatory strategies. A 68-year-old male was admitted following a 10-meter fall, sustaining a moderate TBI with a temporoparietal subdural hemorrhage, a complete C3 vertebral fracture, and significant bilateral pulmonary contusions. His hospital course was marked by acute respiratory distress and neurological deterioration, with a Glasgow Coma Scale (GCS) score of E3V4M5 and hypoxemia requiring intubation and mechanical ventilation in the intensive care unit (ICU). Management focused on the cautious application of positive end-expiratory pressure (PEEP) to improve oxygenation without exacerbating intracranial pressure (ICP), alongside strict cervical spine immobilization and neuro-monitoring. After eight days of complex critical care, the patient’s prolonged need for mechanical ventilation and significant sputum retention necessitated a percutaneous dilational tracheostomy (PDT) to facilitate respiratory weaning and improve pulmonary toilet. In conclusion, this case underscores the profound difficulty of managing concurrent lung and brain injuries in the context of cervical instability. The successful navigation of this trauma triad hinged on a highly individualized, multidisciplinary approach, with judicious ventilator management and timely procedural intervention like PDT being pivotal. It affirms the need for integrated care protocols that can dynamically balance competing organ-system priorities in complex geriatric trauma.